2005
DOI: 10.1016/j.molbrainres.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Gene array profiling of large hypothalamic CNS regions in lactating and randomly cycling virgin mice

Abstract: A dramatic example of neuronal and physiological plasticity in adult mammals occurs during the transition from a non-maternal to a maternal, lactating state. In this study we compared gene expression within a large continuous region of the CNS involved in maternal behaviors (hypothalamus, preoptic regions, and nucleus accumbens) between lactating (L) (postpartum Day 7) and randomly cycling virgin (V) outbred mice. Using high density oligonucleotide arrays representing 11,904 genes, two statistical algorithms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
6
20
0
Order By: Relevance
“…Our results also indicate that these maternal-experience dependent changes in maternal care are associated with an upregulation of gene expression ( Crebbp , Esr2 , Oxt , Avp , and Avpr1a ) in the MPOA, and SB also reduced the amount of maternal experience required to promote the expression of 3 of these 5 genes ( Crebbp , Esr2 , and Oxt ). To our knowledge, we are the first to report that experience with infants alone is associated with an upregulation of some of same genes that are typically elevated at birth (Champagne et al, 2001; Champagne et al, 2003; Gammie et al, 2005; McLeod et al, 2007; Meddle et al, 2007). …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our results also indicate that these maternal-experience dependent changes in maternal care are associated with an upregulation of gene expression ( Crebbp , Esr2 , Oxt , Avp , and Avpr1a ) in the MPOA, and SB also reduced the amount of maternal experience required to promote the expression of 3 of these 5 genes ( Crebbp , Esr2 , and Oxt ). To our knowledge, we are the first to report that experience with infants alone is associated with an upregulation of some of same genes that are typically elevated at birth (Champagne et al, 2001; Champagne et al, 2003; Gammie et al, 2005; McLeod et al, 2007; Meddle et al, 2007). …”
Section: Discussionmentioning
confidence: 90%
“…Further, individual differences in licking and grooming of pups is linked with expression of estrogen receptors in MPOA. Although there is some evidence that an increase in Esr2 expression in the MPOA is associated with increased maternal behavior during the postpartum period (Champagne et al, 2001; Champagne et al, 2003; Gammie et al, 2005; McLeod et al, 2007; Meddle et al, 2007), the role of Esr1 in mediating the quality of maternal care has been described more extensively (Champagne et al , 2001; Champagne et al , 2003). …”
Section: Discussionmentioning
confidence: 99%
“…It is known that during lactation intake is regulated by a number of neuropeptides in the hypothalamus -including neuropeptide Y (NPY) (Malabu et al, 1994;Pickavance et al, 1999;García et al, 2003;, agouti-related peptide (AgRP) (Chen et al, 1999;Phillips and Palmiter, 2008), pro-opiomelanocortin (POMC) (Smith, 1993) and cocaine-and amphetamine-regulated transcript (CART), which are strongly expressed in the arcuate nucleus and dorsomedial hypothalamus (Brogan et al, 2000). These neuropeptides interact with melanocortin receptor populations in the paraventricular nucleus as well as systems in the brain stem and reward centres of the dopaminergic system in the nucleus accumbens (Gammie et al, 2005;Xiao et al, 2005). The argument in the saturated neural control hypothesis was that this regulatory system in the brain may be stimulated by a number of peripheral signals.…”
Section: New Ideas On Limits To Sustained Energy Intakementioning
confidence: 99%
“…For two previous maternal microarrays performed by us on whole septum (Zhao et al, 2012b) and preoptic/hypothalamic tissue (Gammie et al, 2005), significant enrichment was found with top 700 maternal genes, which again highlights a conserved maternal gene expression signature. Supplementary Table 1 provides a list of the gene matches.…”
Section: Comparisons To Other Maternal Brain Microarray Studiesmentioning
confidence: 55%